BILINGUALISM AS A TOOL FOR EFFECTIVE ENGLISH LEARNING (Ustozlar uchun, 2025)
This article explores the role of bilingualism as a powerful facilitator in learning English, emphasizing how the knowledge of two or more languages enhances cognitive performance, linguistic awareness, and communicative competence. Bilingual learners often demonstrate superior metalinguistic understanding, which accelerates the acquisition of English grammar, vocabulary, and pronunciation. Despite these advantages, challenges such as language interference, code-switching, and uneven proficiency levels can arise. The article highlights both the strengths and potential difficulties of bilingual learners, arguing that with appropriate pedagogical support, bilingualism becomes a significant asset in effective English language learning.